Trends in the Integration of Augmented Reality and Artificial Intelligence in Science Education: A Bibliometric Analysis, 2017–2026 - Dhian Andriani; Esmar Budi; Bambang Heru Iswanto; Firmanul Catur Wibowo; Rico Pratama Putra (Universitas Lambung Mangkurat, 2026)
Recent digital advancements have transformed education, making Artificial Intelligence (AI) and Augmented Reality (AR) essential tools for improving the quality of science learning, as demonstrated through bibliometric analysis. This study investigates the evolution of publication trends, identifies the most productive journals, authors, institutions, and countries, determines the most influential publications based on citation counts, analyzes dominant research themes and keyword patterns, and traces the development of research themes in science education from 2017 to 2026. A total of 67 Scopus-indexed documents were selected through purposive sampling. Publication metadata, including titles, abstracts, keywords, citations, and affiliations, were analyzed in RStudio using the bibliometrix package. The findings indicate a substantial increase in publications, with 66 of the 67 articles (approximately 99%) published after 2020 and a peak in 2025. Citation analysis identified the most influential publications, while keyword analysis revealed dominant themes such as student engagement, adaptive learning, and AI-AR-based digital learning media. This study delineates the intellectual structure of AI and AR research in science education and offers practical recommendations for the development of technology-based adaptive learning models. This study investigates (1) the evolution of publication trends on AR and AI in science education from 2017 to 2026; (2) the most productive journals, authors, institutions, and countries; (3) the most influential publications based on citation analysis; (4) dominant research themes and keyword patterns; and (5) the evolution of research themes over time. This study reviewed 67 documents from the Scopus database covering the period 2017 to 2026 and analyzed them using RStudio. The findings indicate a substantial increase in publications addressing the integration of AI and AR in science education over recent years. The analysis also reveals that existing studies consistently highlight the potential of AI and AR to enhance student engagement and learning effectiveness.